2016
DOI: 10.13189/ujer.2016.041205
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Using Instructional Video Games on EFL Learners' Vocabulary Retention

Abstract: This study aimed at investigating the impact of Instructional Video Games (IVGs) on the vocabulary retention of Iranian language learners. To do so, 32 male and 43 female, between the ages thirteen to thirty one years old, in Padideh Derakhshan Institute, Sahinshahr, Isfahan, Iran were selected as a whole population. First, the World English placement test was administered, and 60 learners were chosen as the participants of the study. Next, a test of novelty as a pretest of vocabulary was administered at the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Both in the surveys and in the focus group, all students mentioned that the competitiveness of the game and desire to win and accumulate more points to be among the top five scores at the end of the course had motivated them to study more; this became evident in the students' interest to know about other resources to learn or practice vocabulary outside the class. What was observed is consistent with the findings of the studies carried in [22,28,29] which it is concluded that games motivate and increase interest in learning vocabulary.…”
Section: Influence Of the Materials On The Vocabulary Learning Processsupporting
confidence: 91%
See 2 more Smart Citations
“…Both in the surveys and in the focus group, all students mentioned that the competitiveness of the game and desire to win and accumulate more points to be among the top five scores at the end of the course had motivated them to study more; this became evident in the students' interest to know about other resources to learn or practice vocabulary outside the class. What was observed is consistent with the findings of the studies carried in [22,28,29] which it is concluded that games motivate and increase interest in learning vocabulary.…”
Section: Influence Of the Materials On The Vocabulary Learning Processsupporting
confidence: 91%
“…Besides, another strategy used to promote the acquisition of vocabulary is the integration of videogames and serious games because they not only help motivate students but also allow them to advance at their own pace and according to their skills [22]. Furthermore, the proactive role that the student plays in the game helps the processing of all aspects related to learning a word, which has a positive impact on vocabulary learning and memory.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the reason, failures in language learning are likely due to poor retention of learned information rather than a deficit in initial learning. Although performance on vocabulary recognition tends to be high immediately after training (Brown et al, 2012), performance significantly decreases as the testing delay increases (Salavati, 2016). Thus, improvement of retention is critical for designing more effective language learning programs.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of digitalization and integration of information and communications technology (hereafter ICT) tools in the learning/teaching process, and the call for students-centered approach, students willingly expose themselves to vocabulary unconsciously and deal with the new words in real situations. Therefore, acquiring sufficient vocabulary promotes intelligible communication (Salavati & Salehi, 2016;Wu & Huang, 2017) because vocabulary is considered the basis that links the four language skills together (Wulanjani, 2016). However, the acquisition of new vocabulary for English as a foreign language ( EFL) learning may be challenging (Derakhshan & Khatir, 2015).…”
Section: Introductionmentioning
confidence: 99%